The mediating impact of Halal logistics on supply chain resilience: An agency perspective - Aigbogun, Osaro; Ghazali, Z.; Razali, R. (2016)
This study examines the impact of Halal logistics on supply chain resilience. The study is underpinned by the agency theory. Halal logistics was studied as an Agent of governance and control in the multiple principal-agent model that exists in a typical supply chain. A field survey has been conducted and the research population is the Malaysian pharmaceutical industry. 10 organizations were surveyed. The survey instrument is a structured self-administered questionnaire. The responses were quantified using fuzzy analytical hierarchy process approach. A fuzzy logic method was used to measure the resilience of each organization. Pearson’s correlation and multiple regression analysis were then carried out on SPSS to test the research hypothesis. The results have found that Halal logistics which acts as a governing mechanism for regulation and control in the supply chain, mediates the relationship between each of capabilities and vulnerabilities (predictors) and supply chain resilience (outcome).